Goal shot velocities in elite water polo under competitive match conditions - Hochstein, S.; Hohenstein, D.; Hohmann, A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Throwing performance represents one of the most important performance requirements in elite water polo. The subject of this game analysis was the throwing behavior of the world class players under competition match conditions during the final "World Cup Water Polo" tournament 2018 in Berlin - as well as any differnces to the competition-specific throwing behavior (throwing situation, position, target, speed, as well as precision) of the top European nations Croatia, Serbia, and Hungary.